The Study of Optimization of Flocculation and Destabilization Technology of Waste PEM Drilling Fluid in Bohai Oilfield - Liu, Yang; Zhang, Yuchen; Xie, Tao; Yue, Ming; Wang, Dongsen; Li, Bin (Frontiers in Energy Research, 2021)
In light of the difficulty of solid-liquid separation of waste PEM drilling fluid in the Bohai oilfield, constructing an inorganic-organic flocculation system is proposed and the processing method of destabilization technology is optimized. The biggest influence factor on the flocculation process of PEM drilling fluid was determined by designing an orthogonal test. The flocculation mechanism was researched through single factor optimization, combined with zeta potential and particle size distribution test. The results showed that the most significant factors affecting the flocculation of waste PEM drilling fluid were the dosage of inorganic flocculant CaCl2 and flocculation pH value. When the dosage of inorganic flocculant CaCl2 was 1.2% (w/v), the dosage of organic flocculant SDYJ-2 was 0.05%, the flocculation pH value was 3, and the flocculation time was 5 min, the flocculation technology reached the optimization and then the liquid yield can reach 70.96%. The mechanism of flocculation and destabilization was as follows: the inorganic flocculant of CaCl2 mainly reduced the zeta potential of clay particles through electric neutralization. 1% CaCl2 could reduce the potential mean value of drilling fluid system from -38.1 mV to -32.5 mV, and then decrease the repulsion among suspensions. Through bridging curling and electric neutralization, the organic flocculant of SDYJ-2 can absorb and wrap the clay particles after flocculation destabilization to form a network spatial structure, which made clay particles aggregate into large flocs and particles. D50 can increase by 21.5 times, when the concentration of SDYJ-2 was 0.15%.